2021
DOI: 10.1111/1365-2656.13633
|View full text |Cite
|
Sign up to set email alerts
|

On this side of the fence: Functional responses to linear landscape features shape the home range of large herbivores

Abstract: 1. Understanding the consequences of global change for animal movement is a major issue for conservation and management. In particular, habitat fragmentation generates increased densities of linear landscape features that can impede movements.2. While the influence of these features on animal movements has been intensively investigated, they may also play a key role at broader spatial scales (e.g. the home range scale) as resources, cover from predators/humans, corridors/barriers or landmarks. How space use re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 91 publications
0
7
0
Order By: Relevance
“…By contrast, none of the landmarks tested seemed to be used by migrant ibex as compass for navigation during migration. Yet, recent studies revealed how natural landscape features can be used by mountain ungulates, including Alpine ibex, to delimit their seasonal home ranges and constitute cognitive maps to gather and memorize spatially explicit information for navigation (Seigle-Ferrand et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, none of the landmarks tested seemed to be used by migrant ibex as compass for navigation during migration. Yet, recent studies revealed how natural landscape features can be used by mountain ungulates, including Alpine ibex, to delimit their seasonal home ranges and constitute cognitive maps to gather and memorize spatially explicit information for navigation (Seigle-Ferrand et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…We recorded crossings for all three species, with eland and springbok regularly trespassing the VCF. Permeable fences are often crossed by ungulates and other wildlife (e.g., Kesch et al, 2014Kesch et al, , 2015Dupuis-Desormeaux et al, 2018;Jones et al, 2019;Seigle-Ferrand et al, 2021), although their movement patterns are affected (e.g., McKillop and Sibly, 1988;Harrington and Conover, 2006;Sawyer et al, 2013;Laskin et al, 2020;Wilkinson et al, 2021). Permeable fences may not act as a general barrier but as an obstacle which leads to altered behavior and, consequently, energy expenditure.…”
Section: Direct E Ects Of Wildlife-fence Interactions On Energy Expen...mentioning
confidence: 99%
“…They fragment habitats, shape environments (e.g., Pirie et al, 2017), cause injuries and mortality to wildlife (e.g., Harrington and Conover, 2006;Mbaiwa and Mbaiwa, 2006;Aquino and Nkomo, 2021;McKay et al, 2021) and impede animal movements across various temporal and spatial scales. Short-term foraging (Vanak et al, 2010) and seasonal migratory movements (Sawyer et al, 2013;Nandintsetseg et al, 2019;Seigle-Ferrand et al, 2021) are constrained, redirected to less suitable habitats, or even eliminated by fences. This holds especially true for wild ungulates, as many species track resources across vast areas by following landscape-wide wavelike greening patterns (e.g., Bischof et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we define four broad categories. Physical and disruptive barriers: static human infrastructure such as fences, roads, towns, and dams directly reduce animal movement, increase habitat fragmentation, and reduce ecosystem connectivity (Jakes et al 2018). Even where physical barriers do not exist, disruptive linear features in the landscape, such as roads, have been shown to reduce animal home‐range size (Seigle‐Ferrand et al 2022). Where animals congregate in large numbers, C storage and N fixation can be impeded (Veldhuis et al 2019 b ).…”
Section: Anthropogenic Impacts On Element Redistribution and Stoichio...mentioning
confidence: 99%